The comparative diagnostic and therapeutic application value of FAPI PET/CT and 18F-FDG PET/CT in oncology - Yao, Yongqi; Zhao, Jiawei; Xiao, Jingjing; Chen, Yujing; Guo, Xiaotong; Zhang, Jingyi; Wu, Peitao; Liu, Lixuan; Zhang, Juzheng; Yang, Jinfeng; Chen, Chunrong; Jin, Jiamin; et al. (Frontiers in Oncology, 2026)
Molecular imaging has become central to oncologic diagnosis and therapy assessment. 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) is widely implemented, yet performance is attenuated in tumors with low glycolytic activity or in sites with high physiological uptake. Small-molecule fibroblast activation protein inhibitors (FAPI) enable high-contrast imaging of cancer-associated fibroblasts within the tumor stroma, offering rapid clearance and favorable biodistribution. This review synthesizes clinical and preclinical evidence comparing FAPI PET/CT with18F-FDG PET/CT across solid tumors. Head-to-head analyses indicate superior or complementary lesion conspicuity for FAPI in pancreatic ductal adenocarcinoma and colorectal cancer (CRC) —especially peritoneal and nodal disease—and context-dependent comparability in breast and head-and-neck cancers. Across studies, FAPI demonstrates higher tumor-to-background ratios and improved detection of small or low-FDG-avid lesions, with variable downstream effects on staging and management. We delineate disease-specific scenarios in which multi-tracer strategies may optimize diagnostic yield and propose a framework for integrating FAPI into precision imaging pathways. Priority areas include prospective, adequately powered trials; harmonized acquisition and quantification protocols; and evaluations of cost-effectiveness and theranostic implications.